2007
DOI: 10.1108/13664380780001092
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the impact of risk on project cost overrun in the Nigerian construction industry

Abstract: One of the major reasons for ineffective project delivery in the Nigerian construction industry is the improper assessment of risk factors. As a result, the industry continues to suffer poor performance with many projects failing to meet time and cost targets.• This paper identifies the risk factors inherent in different building procurement methods and assesses their perceived relative importance with a view to evaluating their impact on project cost. The paper reports on a study carried out through a questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 10 publications
(6 reference statements)
0
15
0
Order By: Relevance
“…This factor accounts for 14.78% of variance explained among all barriers (Table 5). According to Dada and Jagboro (2007), the traditional method is the most used in procuring construction projects in Nigeria. In the traditional procurement process, project teams are formed on an ad-hoc basis.…”
mentioning
confidence: 99%
“…This factor accounts for 14.78% of variance explained among all barriers (Table 5). According to Dada and Jagboro (2007), the traditional method is the most used in procuring construction projects in Nigeria. In the traditional procurement process, project teams are formed on an ad-hoc basis.…”
mentioning
confidence: 99%
“…Cases: the Constanta Water Project (Arrowsmith, 2011), Prescom in Targoviste project (Arrowsmith, 2011) Government discontinuity Hertogh and Westerveld (2011), Flyvbjerg et al (2003a, 2003b Lack of political support Curtis and Sturup (2012), Frick (2008), Flyvbjerg et al (2003aFlyvbjerg et al ( , 2003b Cases: Constanta Water project ((Arrowsmith, 2011)), Prescom project ((Arrowsmith, 2011)) Political indecision Dada and Jagboro (2007), Ruuska et al (2009), Haynes (2002 (continued on next page) 2015). In addition, the ANP has been widely used in solving many other complicated decision problems.…”
Section: Political Opposition/interferencesmentioning
confidence: 97%
“…The adoption of informal as against holistic approaches to risk management in PPP have not been effective thereby resulting into project time and cost overruns, low quality of housing units. Studies have reported that improper risk assessment and treatment are among the major reasons for failure of PPP projects and ineffective project delivery in the construction industry in Nigeria (Dada and Jagboro, 2007;Awodele et al, 2009). Risk management should be done proactively and consistently throughout projects' life cycle in order to help in preventing expected risks and to mitigate the impact of threats should those risks occur.…”
Section: ____________________________________________________________mentioning
confidence: 99%